Cosmo-psycho-logos of Tuva in the language of heroic epics - Kuchukova, Zukhra A.; Berberova, Liana B. (The New Research of Tuva, 2023)
The article presents and analyzes the content of the monograph “Features of the Language of Tuvan Heroic Epics (In the Comparative Aspect)” by Mengi V. Ondar, published in 2022 in Abakan. The relevance of the work is determined by addressing the problem of revitalization of the archetypal lexical and semantic layers of minority languages geographically related to the Siberian area of the Russian Federation. The method of comparative analysis of epic texts using modern digital technologies (AntConc program) was highly appraised. The monograph is an innovative and productive research work. It is characterized by its compositional harmony, original research conception, strict academic style of presentation of the materials and the author’s awareness in the categories of related sciences (history, geography, ethnology, cultural studies). The retrospective part of the work covers a whole range of issues related to the history of the collection of materials and publications, the introduction of Tuvan heroic tales into scholarly discourse, as well as the unification of folklore terminology. The thesis about the fruitfulness of comparative studies has been proven and supported by the practice of multilevel analysis of Tuvan and South-Siberian Turkic heroic epics in order to determine ethnolinguistic and cultural similarities and differences. The high-frequency anthroponymic, toponymic and military lexical units identified with the help of the concordance program are carefully interpreted and used in arguments about the existence of similar models of linguistic categorization of the world that historically developed among the Tuvans, Altaians, Shors, Khakas and Mongols. A similar working algorithm was used for the objectification of such structural units as ‘cliché-space’, ‘cliché-time’, ‘cliché — iconic characteristic’, ‘beginning’, ‘ending’. It was supported by vivid illustrative examples from the corresponding epic texts. The monograph contains a series of tables that clearly reflect the results of the author’s comparative studies. In terms of its content, the work of Mengi V. Ondar is close to the philosophical conception proposed by Georgi D. Gachev about the “Cosmo-Psycho-Logos” and stimulates further research in this direction taking into account the folklore and language systems of other peoples of Russia and the world.
Keywords: review; Tuvan heroic epos; Tuvan language; digital research; comparative studies; anthroponym; toponym